Structure-based virtual screening of chemical libraries as potential MELK inhibitors and their therapeutic evaluation against breast cancer. (1st May 2023) - Das, Amiya; Prajapati, Anita; Karna, Amarnath; Sharma, Hitesh Kumar; Uppal, Sheetal; Lather, Viney; Pandita, Deepti; Agarwal, Pallavi
Abstract: New targeted therapy for triple negative breast cancer (TNBC) is an urgent need, as advanced disease responds poorly to conventional chemotherapy. Genomic and proteomic studies are currently investigating new genes and proteins as promising therapeutic targets. One of such therapeutic targets is a cell cycle regulatory kinase; Maternal Embryonic Leucine Zipper Kinase (MELK), overexpressed in TNBC and correlated with cancer development. We performed molecular docking for virtual screening of chemical libraries (phytochemicals/synthetic drugs) against MELK protein structure and identified 8 phytoconstituents (isoxanthorin, emodin, gamma-coniceine, quercetin, tenuazonic acid, isoliquiritigenin, kaempferol, and Nobiletin) and 8 synthetic drugs (tetrahydrofolic acid, alfuzosin, lansoprazole, ketorolac, ketoprofen, variolin B, orantinib, and firestein) as potential hits interacting with the active site residues of MELK based on bound poses, hydrogen bond, hydrophobic interactions and MM/GBSA binding free energies. ADME and drug-likeness prediction further identified few hits with high drug-likeness properties and were further tested for anti-tumorigenic potential. Two phytochemicals isoliquiritigenin and emodin demonstrated growth inhibitory effects on TNBC MDA-MB-231 cells while much lower effect was observed on non-tumorigenic MCF-10A mammary epithelial cells. Treatment with both molecules downregulated MELK expression, induced cell cycle arrest, accumulated DNA damage and enhanced apoptosis. The study identified isoliquiritigenin and emodin as potential MELK inhibitors and provides a basis for subsequent experimental validation and drug development against cancer. Graphical abstract: Image 1 Highlights: Virtual screening identified potential synthetic & phytohits as MELK inhibitors. Hits were refined based on the MM/GBSA energies & ADME drug-likeness parameters. Emodin & Isoliquiritigenin showed excellent MELK binding ability and drug-likeness. Emodin & Isoliquiritigenin induced DNA damage/apoptosis in TNBC cell lines.